For a Mental Emancipation (KULT_online, 2020)
Not a day goes by without the media revealing acts of physical aggression against people simply because of their skin color, religious affiliation or their origin. Over time we have become almost accustomed to this kind of news. Yet despite being denounced, nothing changes – the situation gets worse and worse. This is why Etienne Achille and Lydie Moudileno have jointly published their essay Mythologies postcoloniales: Pour une décolonisation du quotidien in which they try no longer to denounce, but to understand the causes of this phenomenon and provide solutions. The fact that French society does not think of race as a product of the imagination is, in itself, already a real problem. Moreover, by paying attention to false problems such as those related to behaviors or language, we end up forgetting the real one. By adopting a postcolonial approach, the authors analyze aspects and factors in contemporary French society that constitute racial myths or prejudice that delay the process of de-racialization.